Automedicação em gestantes acompanhadas em estratégias de saúde da família da região metropolitana de Fortaleza, Ceará, Brasil - Portácio, Sylas Rhuan Pereira Soares da Silva (2022)
Therapeutic practices in health are generally configured in drug therapies. That is because drugs have the purpose of keeping health in balance, promoting healing, relieving symptoms, and preventing disease. In pregnancy, drugs should only be used when there is an obvious benefit to mother or fetus, the drug has been being produced for a long period of time and if it is considered safe with regard to the emergence of adverse effects in the exposed population. This study aimed to identify the profile of pregnant women regarding self-medication and the potential relationship with teratogenic outcomes, characterize the categories regarding the risks of the fetus according to the FDA, classify the medications used by pregnant women and detect the main maternal and perinatal care resulting from self-medication in primary care in the urban area, in the city of Pacatuba. Exploratory descriptive study with a quantitative approach, with observational analysis carried out in 9 teams of the Estratégia de Saúde da Família program in city in the metropolitan region of Fortaleza, Ceará. Data were collected in 2020, between June and September. Women were submitted to an individual interview, which was guided by a form containing variables regarding sociodemographic, clinical, pharmacological, obstetric data and on adherence to drug therapy. The profile of the pregnant women in the mentioned municipality, from the perspective of the sample that composed the study, it was noticed that they were grouped in the age group between 18 and 29 years old (totaling 58.1%), had completed elementary school as the most expressive occurrence (36.8%), regarding marital status, it was observed that 70% of them had stable union. About occupation in the social environment and in the employment market, the vast majority performs only unpaid work (domestic services) totaling 53.7% and living on only 1 minimum wage (68.4%). Such characteristics result in fragility of knowledge, discernment of danger and increase the possibility of self-medication throughout pregnancy period. The pharmacist enables the population to have greater access to medication and contributes to its rational use, thus favoring the recovery of health and the prevention and treatment of diseases, as established by the guidelines of the Estratégia de Saúde da Família program, the National Policy on Medicines and the National Pharmaceutical Assistance Policy.